Influence of preharvest calcium spray and postharvest chitosan coating methods on quality of Chinese dwarf cherry (Cerasus humilis (Bge.) Sok) fruits during cold storage. Issue 6 (1st November 2020) - Guo, Chang-E.; He, Yinxia; Cui, Qingyu; Li, Weidong
ABSTRACT: The influences of preharvest calcium spray (PCS) and postharvest chitosan coating (PCC) treatments on the levels of sugar, organic acid, and phenolics were evaluated for Chinese dwarf cherry fruit during cold storage. An orthogonal method was applied using the decay rate as index. The optimised treatment was spraying 2.0% Ca(NO3 )2 solution before 21 d of harvest and postharvest application of 0.1% chitosan coating. Compared to the control group, the PCS+PCC treatment group showed a significantly reduced fruit decay rate at the end of storage. Total sugars (91.3–143.1 mg/g), organic acids (11.3–29.4 mg/g), and phenolic (912.4–2337.5 mg/g) contents in optimised group are averagely higher than those in control group. Glucose (24.7–64.8 mg/g) was the predominant sugar, followed by sucrose and fructose. Malic acid (5.2–22 mg/g) was the predominant acid, followed by succinic, citric, tartaric, and oxalic acid. The total phenolic content was relatively stable from 0 to 30 d, and then decreased. The levels of procyanidin and flavonol exhibited similar trends. The antioxidant activities were positively associated with phenolic contents. These findings suggest that treatment with PCS+PCC could be used commercially for extending the storage time and improve Chinese dwarf cherry quality for up to 30 days.